2021
DOI: 10.1155/2021/2570198
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Robust Nonparametric Triple EWMA Wilcoxon Signed-Rank Control Chart for Process Location

Abstract: The nonparametric (NP) control charts are famous for detecting a shift in the process parameters (location and/or dispersion) when the underlying process characteristic does not follow the distributional assumptions. Similarly, when the cost of estimations is very high and the ranking of observational is relatively simple, the ranked set sampling (RSS) technique is preferred over the simple random sampling (SRS) technique. On the other hand, the NP triple exponentially weighted moving average (EWMA) control ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…[ 14 ] and Rasheed et al . [ 15 ] suggested mixed memory and nonparametric triple EWMA control charts for improved process location monitoring.…”
Section: : Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] and Rasheed et al . [ 15 ] suggested mixed memory and nonparametric triple EWMA control charts for improved process location monitoring.…”
Section: : Introductionmentioning
confidence: 99%
“…Recently, Anwar et al [13] introduced AIB double homogeneously weighted moving average (AIB DHWMA) control chart to monitor process location. Also, Rasheed et al [14] and Rasheed et al [15] suggested mixed memory and nonparametric triple EWMA control charts for improved process location monitoring.…”
Section: : Introductionmentioning
confidence: 99%
“…Recent studies have shown that EWMA-type charts are the most useful tools for researchers. For example, Haq [8], Abbas et al [9], Ali et al [10], Tang et al [11], Haq [12], Rasheed et al [13], Rasheed et al [14], etc., are the few recent references in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Alevizakos et al [9] presented one and twosided TEWMA control chart, observing the time between k ≥ 1 events using the gamma distribution. After that, Rasheed et al [10] and Rasheed et al [11] presented two control charts for efficiently monitoring the process mean.…”
Section: Introductionmentioning
confidence: 99%